Diritto, Ragione, Interpretazione secondo Baldassare Pastore : Qualche osservazione a margine (Società e diritti, 2024)
The complexity of law must be taken seriously by legal science. This is the main lesson of Complessità del diritto, interpretazione, ragione giuridica. According to Baldassare Pastore, law is an interpretative social practice that must be observed from the participant’s perspective. In this paper, in addition to explicating the many shared aspects of the hermeneutic perspective, of which Pastore offers a compelling version, two potential objections are raised. The first is that taking the complexity of law seriously requires looking at it from the outside and not only from the inside. The second is that a complex law is not only ‘ordered’ through reason but also by force.